Paratuberculosis: The Trojan in genetic resources of dairy cattle - Behdad, S; Pakdel, A; Massudi, R (Journal of the Hellenic Veterinary Medical Society, 2025)
Mycobacterium avium subspecies paratuberculosis, the main cause of paratuberculosis or Johne’s disease is an intestinal granulomatous infection among ruminants. This review will focus on the Johne’s disease in dairy cattle. This disease by global spread is introduced as a 21st-century disease and can be considered a nightmare for dairy breeders. Due to the long incubation period and its high transmissibility from infected animals to others, the disease is detected when most of the animals are infected. The same issue leads to significant financial and economic losses for the breeders. These losses are not only limited to breeders and will affect the economic network of each country but will also result in a great loss for the export programs of the producing countries. The lack of an accurate diagnostic method has made the management and prevention of Johne’s disease difficult. In recent years, special attention has been paid to managing and reducing side effects caused by this disease and efforts to find accurate, fast, and available diagnostic methods for this infection have increased. This study tries to review various aspects of the economic losses, the threat of this infection for genetic resources and breeding programs, and introduce novel physical diagnostic methods to prevent losses caused by this disease.